2015
DOI: 10.1093/mnras/stv366
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the dynamics of a giant Ly α halo at z = 4.1 with MUSE: the energetics of a large-scale AGN-driven outflow around a massive, high-redshift galaxy

Abstract: Citation for published item:winnkD eF wF nd ernetD tF hF F nd milD sn nd he freukD gF nd fonD F nd gontiniD F nd ihrdD tF nd ¤ ottgeringD rF tF eF nd rrutiD F nd enemnsD fF @PHISA 9wpping the dynmis of gint vy lph hlo t z a RFI with wi X the energetis of lrgeEsle eqxEdriven out)ow round mssiveD highEredshift glxyF9D wonthly noties of the oyl estronomil oietyFD RRW @PAF ppF IPWVEIQHVF Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 90 publications
(132 reference statements)
7
54
0
Order By: Relevance
“…Such extended Lyα haloes have been detected in several other HzRGs (e.g. van Ojik et al 1996;Reuland et al 2003;Swinbank et al 2015). The Lyα halo in MRC0943-242 shows a linear filament, Bifrost, connecting Yggdrasil with the two brightest dust continuum components (Thor and Odin), strongly suggesting that they are physically connected (see Fig.…”
Section: Ionised Gasmentioning
confidence: 59%
“…Such extended Lyα haloes have been detected in several other HzRGs (e.g. van Ojik et al 1996;Reuland et al 2003;Swinbank et al 2015). The Lyα halo in MRC0943-242 shows a linear filament, Bifrost, connecting Yggdrasil with the two brightest dust continuum components (Thor and Odin), strongly suggesting that they are physically connected (see Fig.…”
Section: Ionised Gasmentioning
confidence: 59%
“…Decarli et al (2016) and Aravena et al (2016) observed a comparable shift in the compact starforming galaxy ASPECSC.1 (z=2.54). In a similar fashion, the Lyα extended emission not associated with the radio jet, the rest-frame UV continuum, and the dust emission (albeit the coarse spatial resolution) appear to be offset in the z=4.11 radio galaxy TNJ1338−1942(e.g., De Breuck et al 2004Zirm et al 2005;Venemans et al 2007;Swinbank et al 2015).…”
Section: The Host Galaxy Of J0305−3150mentioning
confidence: 99%
“…The intrinsic brightness of these objects makes it possible to probe deeply into the physics of the gas, even to resolve the spatial variation of the Ly α line at kpc scales (e.g. Weijmans et al 2010;Swinbank et al 2015;Prescott et al 2015), but ideally, one would like to pursue similar studies on typical high redshift galaxies, which requires a very high signal-to-noise only achievable with the next generation of ground-based optical and near-infrared telescopes.…”
Section: Introductionmentioning
confidence: 99%